Factors Affecting Employee Performance in Startups Under VUCA Conditions - Hendra Etri Gunawan; Arif Imam Suroso; Suhendi (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The digital economy represents a new source of growth for many countries, including Indonesia. In Indonesia, the digital economy continues to expand, with startups serving as one of its main drivers. However, as technology-based enterprises, startups often face low business success rates due to volatile, uncertain, complex, and ambiguous (VUCA) conditions. Purpose: This study aims to examine the relationship between firm/environment-related factors (training culture, management support, and organizational climate), job-related factors (work environment, job autonomy, and job communication), and employee-related factors (intrinsic motivation, proactivity, and adaptability) on employee performance.Design/methodology/approach: The study was conducted from December 2024 to February 2025 by distributing questionnaires to 93 startup employees via Google Forms. The data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with two main stages: outer model evaluation (lower-order and higher-order constructs) and inner model evaluation.Findings/Results: The results indicate that only job-related and employee-related factors have a positive and significant impact on employee performance. Furthermore, these factors serve as key mediators in the relationship between firm/environment-related factors and employee performance.Conclusion: Strategic priorities for enhancing employee performance include optimizing the management of both job-related and employee-related factors.Originality/value (State of the art): This study specifically investigates the interplay between firm/environment-related, job-related, and employee-related factors and their collective impact on employee performance in startup environments. Ultimately, it aims to formulate actionable strategies for improving employee performance in startups operating under VUCA conditions, thereby contributing to broader business and organizational success. Keywords: digital economy, employee performance, VUCA, SEM-PLS, startup environments